Analysis of Carbohydrate, Protein and Water Content in Peanut Cookies Substituted with Red Beans And Sesame As An Alternative Snack For Toddlers - Vifta Fatih Ma'rifah; Amalia Ruhana (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Background: Peanut cookies food product development is one alternative in overcoming the problem of malnutrition in toddlers. Purpose: This study aims to determine the carbohydrate, protein, and water content of peanut cookies substituted for red beans and sesame. Methods: This study is a pure experimental study (true experiment). The experimental research method uses a completely randomized design (CRD) with 3 treatments and 1 control. The proportion of red beans and sesame in each treatment is 40%: 10%, 35%: 15%, and 30%: 20%. Analysis of carbohydrate, protein and water content was carried out at the Food Analysis Laboratory of Jember State Polytechnic. The method of analysis of nutrient content used is in accordance with SNI 01-2891-1992, namely carbohydrates using the Luff Schoorl method, protein using the kjeldahl method, and water using the oven method. Data on nutrient content were analyzed using descriptive analysis. Result: The results of the analysis of nutrient content showed that in the first treatment there was a carbohydrate content of 41.31%, protein of 11.31% and water of 3.63%. In the second treatment, there was a carbohydrate content of 38.04%, protein of 12.66%, and water of 3.73%. While in the third treatment, there was a carbohydrate content of 34.58%, protein of 13.82%, and water of 3.77%. Conclusion: From all treatments, the three nutritional contents have met the quality requirements of cookies according to SNI 2973:2022.